Acceleration Method And Its Application On Self Life Determination Of Starfruit Juice Packed In Glass Bottle - Syarifah Aminah; Tezar Ramdhan; Mulihani Yanis (Buletin Teknologi Pasca Panen, 2013)
Shelf lifeis usually known by the public as expire date, which marked by the date, month and year on the product packaging. According to UU No. 18/2012 about Food, expire date is one of the information that must be included by the manufacturers/ producers on the packaging label of food products. The paper explains about the most widely used method of shelf life determination in the food industries, it is the acceleration method using the Arrhenius model. Arrhenius model simulate the accelerated destruction of the product under conditions of high temperature storage (above normal storage temperature). The rate of chemical reactions that can lead to damage of food products generally follow there action rate of the order 0 and order 1. Application of acceleration method on self life determination of starfruit juice packed in glass bottle using vitamin C as critical parameter during storage at different temperatures. Abstrak Versi IndonesiaMetode Akselerasi dan Aplikasinya Pada Pendugaan Umur Simpan Sari Belimbing Dalam Kemasan Botol Gelas Umur simpan biasanya dikenal oleh masyarakat dengan istilah masa kadaluarsa yang berisi informasi tanggal, bulan dan tahun yang tercantum pada kemasan produk. Menurut Undang-undang No. 18 tahun 2012 tentang Pangan, informasi tersebut wajib dicantumkan oleh produsen pada label kemasan produk pangan. Dalam makalah ini ditelaah mengenai metode penentuan umur simpan yang paling banyak digunakan di industri pangan, yaitu metode akselerasi dengan menggunakan model Arrhenius. Model Arrhenius mensimulasikan percepatan kerusakan produk pada kondisi penyimpanan suhu tinggi di atas suhu penyimpanan normal. Laju reaksi kimia yang dapat memicu kerusakan produk pangan umumnya mengikuti laju reaksi ordo 0 dan ordo 1. Aplikasi metode akselerasi pada pendugaan umur simpan sari belimbing dalam kemasan botol gelas dilakukan terhadap parameter vitamin C sebagai titik kritis pada suhu penyimpanan yang berbeda.